Perspectives of professionals on the perinatal period as a window of opportunity for change in women with SUD: insights from healthcare, child welfare, substance use, and child protection services - Vandewalle, Sarah; Rowaert, Sara; Lemmens, Gilbert; De Pauw, Sarah; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2026)
IntroductionThe perinatal period is widely recognized as a time of profound transition and heightened vulnerability, particularly for women with substance use disorders (SUD). Adopting a strengths-based perspective, this qualitative study aims to explore how professionals across healthcare, child welfare, substance use, and child protection services in Belgium perceive this period as a window of opportunity for change in women with SUD.MethodSemi-structured interviews were conducted with 43 professionals, and thematic analysis identified key themes related to barriers, opportunities, and facilitators to achieve change.ResultsBarriers include disconnected bodily awareness, mutual avoidance between women and professionals, limited insight and (self-) reflection on SUD and motherhood, and insufficient support across interpersonal, socioeconomic, and systemic levels. However, professionals also identified several areas that could be reinforced to unlock the period’s transformative potential, reflecting a gradual shift from a deficit-oriented view toward a more strengths-based understanding of perinatal SUD. Empowerment was seen as crucial through open conversations on family planning, psychoeducation on fertility and contraception, access to appropriate contraceptives, and trauma-sensitive, body-oriented approaches that foster connection to pregnancy and the unborn child, as well as the integration of the infant mental health perspective. The perinatal period itself was considered a naturally occurring window of opportunity for change, driven by processes of identity transformation and growing maternal motivation. Professionals emphasized the importance of enhancing professional capacity, particularly in healthcare, and improving screening and referral by midwives and gynecologists. At the care system level, increased and more consistent contact with healthcare services during pregnancy was described as a contextual opportunity for timely support; however, intersectoral collaboration and integrated care were considered essential, alongside a legal prenatal framework that enables early, non-punitive interventions to support both mother and (unborn) child.DiscussionThese findings underscore the need to move beyond hegemonic discourses that frame strength and deficit, mothering and substance use, or vulnerability and opportunity as binary opposites. Recognizing the ways these dimensions coexist and intersect is vital for developing responsive, relational, and ethically grounded models of perinatal care.